Electron Trapping in Magnetic Mirror Structures at the Edge of Magnetopause Flux Ropes. Issue 4 (28th April 2021) - Robertson, S. L.; Eastwood, J. P.; Stawarz, J. E.; Hietala, H.; Phan, T. D.; Lavraud, B.; Burch, J. L.; Giles, B.; Gershman, D. J.; Torbert, R.; Lindqvist, P.‐A.; Ergun, R. E.; et al.
Abstract: Flux ropes are a proposed site for particle energization during magnetic reconnection, with several mechanisms proposed. Here, Magnetospheric Multiscale mission observations of magnetic mirror structures on the edge of two ion‐scale magnetopause flux ropes are presented. Donut‐shaped features in the electron pitch angle distributions provide evidence for electron trapping in the structures. Furthermore, both events show trapping with extended 3D structure along the body of the flux rope. Potential formation mechanisms, such as the magnetic mirror instability, are examined and the evolutionary states of the structures are compared. Pressure and force analysis suggest that such structures could provide an important electron acceleration mechanism for magnetopause flux ropes, and for magnetic reconnection more generally. Key Points: Magnetospheric Multiscale observations show magnetic mirror structures on the edge of magnetopause flux ropes Mirror structures trap electrons and have extended 3D structure Evolution of mirror structures could facilitate particle acceleration